2017
DOI: 10.1097/coc.0000000000000146
|View full text |Cite
|
Sign up to set email alerts
|

CNS Hemangiopericytoma

Abstract: Complete resection followed by adjuvant radiation improves survival. Extraneural metastases, especially to lung, bone, and liver, are not uncommon and can occur late in the disease course for which continued follow-up is required. There is also a need to establish a systemic treatment regimen to control the distant metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(24 citation statements)
references
References 27 publications
(41 reference statements)
0
23
0
Order By: Relevance
“…In our series, the similar gender distribution was seen, which was against the idea that osseous SFT/HPC occurred with a slight predominance among males [1,15,19,20]. In previous reports [6,7], intraspinal HPCs commonly occurred in the cervical and thoracic segments of the spine and rarely in the lumbar and sacral segments.…”
Section: Discussionmentioning
confidence: 39%
“…In our series, the similar gender distribution was seen, which was against the idea that osseous SFT/HPC occurred with a slight predominance among males [1,15,19,20]. In previous reports [6,7], intraspinal HPCs commonly occurred in the cervical and thoracic segments of the spine and rarely in the lumbar and sacral segments.…”
Section: Discussionmentioning
confidence: 39%
“…[8, 12, 27] As previous studies have found, surgical resection alone is sufficient to cure patients in many cases. Although tumour site was not related to DFI in our series, 57% of cases in which GTR was not achieved were located at cranial base, a site which could possibly hamper a complete resection as reported for other CNS tumours (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…[812] Based on these findings, the current WHO grading criteria provide that SFT/HPC with solitary fibrous tumour phenotype and mitotic count <5 mitoses/10 high-power fields (HPF) are classified as grade I, whereas tumours with hemangiopericytoma morphology are graded as grade II or III based on the mitotic count with a cut-off value of 5 mitoses/10 HPF. [1] Radiotherapy may be of benefit to patients with incomplete resection or at higher risk of recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The imaging manifestation of MHP is described as a large solitary solid or cystic-solid irregular mass with uneven density, unclear boundaries, hemorrhage and necrosis. Studies have shown that MHPs can be enhanced in a variety of ways from the early to late phase [ 19 ]. In our study, 2 patients showed obvious heterogeneous enhancement in the arterial phase, which gradually decreased in the portal venous and delayed phases, with no obvious expansion in the enhancement range.…”
Section: Discussionmentioning
confidence: 99%